Towards institutional and organisational framework for the National spatial data infrastructure development in Serbia - Ljiljana Živković (Acta Geographica Slovenica, 2012)
Spatial data infrastructure (SDI) represents a concept that tends to create a context for cooperation and exchange of data, information and knowledge between a particular spatial data community’s stakeholders. Thus, the aim of SDI concept development is to establish a common spatially supported platform for making right decisions relevant for economic progress, good governance and sustainable development within a certain domain or jurisdiction, i.e. administrative level. Today, the majority of launched SDI initiatives are on the national level that is also identified as the crucial one for evolution of this concept in general. Additionally, recent research has proven that national SDI (NSDI) developments have become prevailingly social phenomena since interactions between their stakeholders appeared to be critical for achieving purpose of these initiatives, and SDI concept vision in general. Therefore, the aim of this article is to propose an appropriate social, i.e. institutional and organisational framework, for NSDI development in Serbia.